Termite transects from Buton Island, Sulawesi, have a low diversity compared with Sundaland sites. (4th July 2021) - Hasan, F.; Jones, D. T.; Syaukani, S.; Eggleton, P.
Abstract: We used a standardised transect method to compare lowland forest termite assemblages in Buton Island, Sulawesi, with transects in Sundaland. The four Buton transects were extremely depauperate with species density ranging from 1 to 6 species, which is around 10% of the species density in 11 described Sundaland transects. Soil-feeding species were absent from the Buton transects but represent some 43% of species in the Sundaland transects. The Buton transects have relatively high soil pH (6.7–7.9), which may be associated with depauperate termite assemblages. Most termite genera recorded in Sulawesi are wood nesters that can raft in floating wood, which is probably how they arrived in Sulawesi. The Macrotermitinae (fungus-growers) do not raft and probably flew across serendipitously. Geographic isolation, both on Buton and in Sulawesi more generally, and Buton's underlying geology causing high soil pH, may account for the near-absence of soil-nesters and soil-feeders, none of which are known to raft.